ANALISIS TORSI DAN DAYA AKIBAT PEMOTONGAN RAMP POROS BUBUNGAN (CAMSHAFT) PADA SEPEDA MOTOR SUZUKI SHOGUN 125 SP TAHUN 2005 - Mahmud, Kurniawan Hidayah (Jurnal Nosel, 2012)
Abstract Based on results an analysis of torque and power from the cutting ramp camshaft on motorcycles suzuki shogun 125 sp in 2005, can be concluded that: (1) Maximum torque and power generated using standard camshafts tend to be smaller. The maximum torque produced 6.28 ft-lbs at 6000 rpm rotation, while the maximum power generated is 7.99 ft-lbs at 7500 rpm rotation. Torque produced is small, causing the vehicle less responsive when acceleration, and less power has achieved a maximum speed of the vehicle is lower. (2) Maximum torque and power using modified camshaft (255o duration) tend to be larger. The maximum torque produced 6,98 ft-lbs at 6500 rpm rotation, while the maximum power generated is 9,78 ft-lbs at 8000 rpm rotation. Torque generated large, cause the vehicle more responsive when acceleration, and the power to cause the maximum speed achieved higher vehicle. (3) By using a modified camshaft (255o duration) produces torque and power is better than using a standard exhaust camshafts. The increase in maximum torque after using the modified camshaft of 0,7 ft-lbs, causing the vehicle more responsive when I started running and acceleration. The engine speed to move towards the higher as far as 500 rpm, causing to easily achieved maximum power. Meanwhile, an increase in power after using the modified camshaft, that is equal 1,8 hp, causing a maximum speed causing higher vehicle. The engine speed to move toward a higher rate as far as 500 rpm, causing the maximum speed remains stable.